Integrated care pilot in north west London: a mixed methods evaluation - Natasha Curry (International Journal of Integrated Care, 2013)
Introduction: This paper provides the results of a year-long evaluation of a large-scale integrated care pilot in North West London. The pilot aimed to integrate care across primary, acute, community, mental health and social care for people with diabetes and those over 75 years through: care planning; multidisciplinary case reviews; information sharing; and project management support.    Methods: The evaluation team conducted qualitative studies of change at organisational, clinician, and patient levels (using interviews, focus groups and a survey); and quantitative analysis of change in service use and patient-level clinical outcomes (using patient-level data sets and a matched control study).   Results: The pilot had successfully engaged provider organisations, created a shared strategic vision and established governance structures. However, engagement of clinicians was variable and there was no evidence to date of significant reductions in emergency admissions. There was some evidence of changes in care processes.   Conclusion: Although the pilot has demonstrated the beginnings of large-scale change, it remains in the early stages and faces significant challenges as it seeks to become sustainable for the longer term. It is critical that NHS managers and clinicians have realistic expectations of what can be achieved in a relatively short period of time.